Syllable Intonations in the East Aukštaitian and North Žemaitian Dialects: Common Features and Differences - Kačiuškienė, Genovaitė; Girdenis, Aleksas (Kalbotyra, 1997)
In the East Aukštaitian and North Žemaitian dialects the contrast of acute (sharp, falling syllable intonation) and circumflex (smooth, rising intonation) is realized by distinctly different acoustic features.In a diphthongal syllable the main difference of the East Aukštaitian intonations concerns the pronunciation of the first component of the diphthong: this component is strongly reduced (almost diffuse) in the circumflex syllables and nearly coincides with the corresponding monophthong in the acute syllables. The variations of the pure prosodic features may be estimated as negligible.In contrast to this, the North Žemaitian syllable intonations are purely prosodic phenomena. The acute in this dialect can be interpreted as a whole consisting of abruptly falling fundamental frequency (tone) and intensity (energy); the frequency and intensity of the circumflex syllables change (rise and descend) rather gradually.